Effect of High School Showcase Exposures and Timing of Ulnar Collateral Ligament Tear on Professional Baseball Careers in Elite Pitchers. Issue 4 (March 2023) - Kriz, John P.; DeFroda, Steven; Staffa, Steven J.; Kriz, Peter K.
Background: Showcase participation has been considered a risk factor for elbow injuries. It remains unclear whether high school (HS) showcase volume negatively affects pitchers' career paths. Because pitchers are achieving 90 mph thresholds at younger ages, it is unknown whether shorter time intervals between achieving 90 mph thresholds and dates of ulnar collateral ligament reconstruction (UCL-R), known as time to tear (TTT), may affect career trajectory. Hypothesis: Elite pitchers with higher HS showcase volumes would be less likely to reach Major League Baseball (MLB) level compared with elite pitchers with fewer HS showcase appearances. Elite pitchers with longer TTT intervals would be more likely to achieve MLB level. Study Design: Cohort study; Level of evidence, 3. Methods: Demographic, HS showcase and professional performance, and injury data from pitchers selected in the first 5 rounds of the MLB draft (2011-2017) were gathered from publicly available databases. Continuous and categorical variables were compared for the following subgroups: UCL-R group and pitcher group not undergoing UCL-R; "early" and "late" UCL-R groups; and pitchers achieving and pitchers not achieving MLB level. Multivariable analysis was performed using logistic regression. Standard deviations of ±1 SD were used to define early career versus late career UCL-R subgroups after normal distribution was confirmed (Shapiro-Wilk test; P = .227). The early UCL-R group was defined as those pitchers undergoing UCL-R ≤−1 SD from the mean age at first injury (group mean age, 19.43 years), whereas the late UCL-R group was defined as ≥+1 SD from that age (group mean age, 25.19 years). Results: Of 611 pitchers, 455 (74.5%) had HS showcase performance data, and 608 (99.5%) had professional performance data. In total, 184 (30.1%) pitchers underwent UCL-R. Fewer pitchers who underwent early UCL-R achieved the MLB level compared with pitchers who underwent late UCL-R (48.1% vs 86.2%; P = .006). Elite pitchers who pitched in ≥10 showcases in HS had half the odds of achieving the MLB level compared with pitchers who participated in <10 HS showcases (adjusted odds ratio, 0.50; 95% CI, 0.29-0.86; P = .012). For every year longer that an elite pitcher did not tear his UCL after achieving the 90 mph threshold at an HS showcase (TTT after 90 mph [per year]), the likelihood of achieving the MLB level increased by 24% (adjusted odds ratio, 1.24; 95% CI, 1.02-1.52; P = .032). Conclusion: Higher HS showcase volume in elite pitchers was associated with a lower likelihood of achieving MLB level. A longer TTT after 90 mph (per year) was significantly associated with achieving MLB level in elite pitchers.